Basement geology, tectono-stratigraphic and diagenetic evolution of the presalt succession in the Northern Campos Basin, Brazil - Strugale, M (2022)
The Campos Basin (SE Brazil) hosts significant hydrocarbon accumulations in reservoirs above and below a layer of evaporites. The rift to post-rift lacustrine carbonates that constitutes the Pre-Salt reservoirs have been the object of several studies focused on the depositional and diagenetic characteristics of these Barremian to Aptian carbonates. Nevertheless, the basement geology, tectono-stratigraphic evolution and geochronologic constraints for the hydrothermal diagenesis are yet to be established. This thesis presents a novel integrated geological study of the entire presalt sequence utilizing 2D and 3D seismic surveys and sidewall cores from a hydrocarbon accumulation in the northern Campos Basin. The basement is constituted by anisotropic, high-grade supracrustal rocks in the East and relatively isotropic granitic rocks in the West. Lithologies, structural style and age suggest a correlation with the onshore Cabo Frio Tectonic Domain. The overall rift evolution probably started during the Berriasian with a peak of rift-related faulting from the Hauterivian to Barremian, followed by a rift transition and post-rift stages (Barremian to Aptian). The pre-existing metamorphic fabric was selectively reactivated whenever its orientation was favourable. Petrography and geochemistry show diagenetic phases composed predominantly of quartz, calcite and dolomite to ankerite series, and secondarily pyrite, Sr-barite and svanbergite. Additional studies of stable isotopes, fluid inclusion microthermometry and LA-ICP-MS U-Pb geochronology in the diagenetic minerals provide evidence for three tectono-diagenetic events that occurred under distinct diagenetic settings during the Barremian to Aptian, the Albo-Cenomanian and the Campanian to Maastrichtian stages. The diagenetic conditions were initially hydrothermal and progressively attained geothermal equilibrium under deep-burial conditions towards the Late Cretaceous. These diagenetic episodes were not necessarily coeval with magmatic events were are always coeval with basin-scale tectonic events described previously using balanced cross-sections in the post salt section.